Mind-boggling Chicks: Response to a Commentary - Baruss, Imants; Mossbridge, Julia (Journal of Scientific Exploration, 2018)
We very much appreciate Damien Broderick’s kind comments about our book and for this opportunity to engage in a discussion of its substance. Each person has a boggle threshold, which we define in Transcendent Mind as “the degree to which a person is willing to deviate from normative beliefs” (p. 24). In Damien’s case, that threshold appears to lie somewhere beyond laboratory-verified psi phenomena, but on this side of some of the more outrageous phenomena that have been observed in field studies, such as some of the phenomena ostensibly produced by Thomaz Coutinho. So let us start by saying a little bit about the inclusion of the Thomaz material in the book.